Information Communication and Technology: An Introduction - Soegoto, Riswono; Umam, M C; Nurwan, J V; Ismail, E S (International Journal of Research and Applied Technology (INJURATECH), 2024)
This study aims to explain how information communication technology can change the way of communication in the office. It makes it easier to provide information through groups that the office has created so that there is no need to face-to-face to provide information. Communication information technology can change the way to meet face-to-face meetings. It is advanced to being online, like using a laptop and cellphone. The method used in this study was a descriptive method with observation and interviews to obtain the required information. This research shows that the development of ICT can promote communication in the office because it can convey information more effectively and practically. To communicate with each other, they don't need to meet face to face because there is already a media that helps them make it easier. The conclusions obtained in this study are that information technology is very helpful for offices or companies to make it easier to convey information to office employees or office superiors very quickly and practically